The issue of citizenship under the eyes of the indigenous people in the Indigenous Land Cobra Grande, Santarém/PA (Educação e Pesquisa, 2021)
This article discusses the issue of citizenship from the perspective of indigenous people from the Cobra Grande Indigenous Land (TICG, abbreviation in portuguese) who participate in a teacher training course. The question investigated is how indigenous people, who are deeply involved in the Kariwa culture, and having to fight for their rights at all times, including the right to remain indigenous, see the issue of citizenship. The objective of the study was to identify what the indigenous people of TICG understand by the word citizenship and how they perceive the exercise of it in the daily life of the villages. Methodologically, the research fits as an ethnographic case study in education, without, however, being totally reduced to the method, as we investigated, based on a participatory process in which the interlocutors were also researchers. The research process involved preliminary discussions, preparation, application and evaluation of action projects and semi-structured interviews. The results show that the indigenous are concerned with the impact of the TICG indigenous contact with the Kariwa culture and the consequences of this contact for the indigenous way of being and living. The survey also revealed that indigenous people are aware of their rights and understand citizenship both in the right-duty binomial and as an instrument to fight for the preservation of the culture and traditions of the villages.